Evaluation of some predictive parameters for baked-milk tolerance in children with cow's milk allergy - Kilic, Mehmet; Cilkol, Lutfiye; Taskin, Erdal (Codon Publications, 2021)
Background: Inclusion of baked-milk products to the diet appears to markedly accelerate tolerance to unheated milk compared to a strict avoidance diet. Objective: The present study aims to investigate the predictors of baked-milk tolerance in children with Immunogtobutin E (IgE)-mediated cow's milk (CM) allergy. Methods: The study included 80 patients diagnosed with IgE-mediated CM allergy upon oral food challenge (OFC) testing at our clinic. Patients who developed and did not develop reactions during OFC with baked milk were compared considering clinical and laboratory parameters. Results: Eighty patients with CM allergy comprised 48 male and 32 female infants with an average age of 7.25 +/- 2.45 (3-13) months. We found that 62.5% of them showed tolerance to baked milk in the OFC test performed with cakes containing 2.6-g milk protein. When the patients who tolerated and could not tolerate baked-milk products were compared for test results, we detected a statistically significant intergroup difference regarding diameter of wheal in skin prick test (SPT) performed with muffin slurry, levels of specific Immunoglobulin E (sIgE) in CM, sheep's milk (SM), goat's milk (GM), casein, and the amount of unheated milk consumed until a reaction developed in the OFC test performed with unheated milk (P <0.05). Conclusion: We defined novel decision points based on CM, SM, GM, casein sIgE levels, wheal diameter in SPT with muffin slurry, and the amount of milk ingested during OFC performed with unheated milk that may be useful in predicting outcomes of baked-milk ingestion. (C) 2021 Codon Publications. Published by Codon Publications.
Keywords: Children; cow's milk; goat's milk; sheep's milk; predicting; baked milk tolerant; baked; milk reactive